Pain Management in People with Diabetes-Related Chronic Limb-Threatening Ischemia - Xiaoyan Jiang; Yi Yuan; Yu Ma; Miao Zhong; Chenzhen Du; Johnson Boey; David G. Armstrong; Wuquan Deng; Xiaodong Duan (Journal of Diabetes Research)
Management of neuropathic pain in people with diabetes has been widely investigated. However, little attention was paid to address ischemic-related pain in patients with diabetes mellitus who suffered from chronic limb-threatening ischemia (CLTI), the end stage of lower extremity arterial disease (LEAD). Pain management has a tremendous influence on patients’ quality of life and prognosis. Poor management of this type of pain owing to the lack of full understanding undermines patients’ physical and mental quality of life, which often results in a grim prognosis, such as depression, myocardial infarction, lower limb amputation, and even mortality. In the present article, we review the current strategy in the pain management of diabetes-related CLTI. The endovascular therapy, pharmacological therapies, and other optional methods could be selected following comprehensive assessments to mitigate ischemic-related pain, in line with our current clinical practice. It is very important for clinicians and patients to strengthen the understanding and build intervention strategy in ischemic pain management and possible adverse consequence.